PERCUTANEOUS NEPHROLITHOTOMY AND RETROGRADE INTRARENAL SURGERY FOR TREATMENT OF RENAL STONE SIZE BETWEEN 1.0 CM AND 2.5 CM: A COMPARATIVE STUDY - BAHETI, VISHWAS; TRIVEDI, PANKAJ; DOBARIA, UDAY; MEHTA, FATEH SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: To evaluate the efficacy and safety of RIRS and PCNL in treatment of renal stone size between 1-2.5cm. Methods: This comparative prospective study was conducted in the Department of Urology of a tertiary care teaching hospital of Rajasthan from January 2019 to June 2020. Patients were fully informed about the study protocol and a written informed consent has obtained from patients with renal stone disease without any co-morbid conditions, posted for RIRS and PCNL. Stone free rate, post operative complications, hospital stay, operation time and cost between RIRS and PCNL for treatment of renal stone size between 1-2.5cm were compared. Results: Out of total 313 patients, 212 patients underwent PCNL and 101 patients RIRS. The stone clearance rate was significantly better in PCNL (92.45%) than RIRS (85.15%). The hospital stay was significantly less in RIRS (2.02±1.36 days) when compared to PCNL (3.89±2.18 days). Mean operative time for PCNL was significantly less i.e. 71.81±12.89 minutes as compared to 85.79±13.94 minutes in RIRS. Post-operative complications were more in PCNL group than RIRS. Conclusions: This study concluded that PCNL when compared to RIRS both have advantages and disadvantages according to size and location of stone, post-operative complications, stone free rate and operation cost. Judicious use of PCNL and RIRS should be done according to above mentioned parameters.